Vietnam : Technical Assistance Report-National Accounts Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2022)
At the request of the General Statistics Office (GSO) of Vietnam, a technical assistance mission helped with the measurement of the non-observed economy in national accounts. This was part of a series of missions to support the compilation of a new national accounts benchmark for 2020 and publish rebased estimates in March 2023. This mission was funded by the IMF's Data for Decisions project with the overall goal of putting more and better data in the hands of decision-makers.